The Implementasi penilaian berbasis portofolio digital dalam pembelajaran privat bahasa Arab - Laily, Fitry; Himmah, Ro’fat Hizmatul (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This study aims to explore the implementation of digital portfolios in enhancing Arabic language skills among Madrasah Ibtidaiyah students in a private tutoring context at Global Learning Course. Employing a qualitative case study design, the research investigates how digital portfolio-based assessment documents students’ holistic learning progress, including cognitive, affective, psychomotor, and metacognitive domains. The participants consisted of students and Arabic language tutors who had engaged in digital portfolio practices for at least one semester. Data were collected through classroom observations, in-depth interviews, and analysis of students’ digital portfolios. The findings reveal that digital portfolios effectively visualize students’ learning progress and contribute to increased motivation, self-confidence, and active engagement. Moreover, this approach shifts assessment practices from product-oriented to process-oriented evaluation, providing a more authentic and comprehensive understanding of student development. Digital portfolios also support personalized learning and facilitate communication among tutors, students, and parents. However, their successful implementation depends on tutors’ pedagogical and digital competencies as well as the availability of time for meaningful feedback. Abstrak Penelitian ini bertujuan untuk mengkaji penerapan portofolio digital dalam meningkatkan keterampilan bahasa Arab di kalangan siswa Madrasah Ibtidaiyah dalam konteks bimbingan belajar swasta di Global Learning Course. Dengan menggunakan desain studi kasus kualitatif, penelitian ini menyelidiki bagaimana penilaian berbasis portofolio digital mendokumentasikan kemajuan belajar siswa secara holistik, termasuk dalam domain kognitif, afektif, psikomotorik, dan metakognitif. Peserta penelitian terdiri dari siswa dan tutor bahasa Arab yang telah terlibat dalam praktik portofolio digital selama setidaknya satu semester. Data dikumpulkan melalui observasi kelas, wawancara mendalam, dan analisis portofolio digital siswa. Temuan menunjukkan bahwa portofolio digital secara efektif memvisualisasikan kemajuan belajar siswa dan berkontribusi pada peningkatan motivasi, kepercayaan diri, serta keterlibatan aktif. Selain itu, pendekatan ini mengubah praktik penilaian dari orientasi hasil menjadi orientasi proses, sehingga memberikan pemahaman yang lebih otentik dan komprehensif tentang perkembangan siswa. Portofolio digital juga mendukung pembelajaran yang dipersonalisasi dan memfasilitasi komunikasi antara tutor, siswa, dan orang tua. Namun, keberhasilan implementasinya bergantung pada kompetensi pedagogis dan digital tutor serta ketersediaan waktu untuk memberikan umpan balik yang bermakna.